2022
DOI: 10.1002/hyp.14641
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution temporal dynamics of intra‐storm isotopic composition of stemflow and throughfall in a Mediterranean Scots pine forest

Abstract: Vegetation plays a significant role in the isotopic fractionation of rainwater during rainfall partitioning through the canopy into throughfall and stemflow. Most studies focus on the isotopic composition of throughfall, whereas that of stemflow has been studied much less frequently. Moreover, only three studies to date have investigated stemflow isotopic composition at the intra‐storm scale. Therefore, knowledge of the isotopic shift between rainfall and throughfall/stemflow at fine resolutions is sorely need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 49 publications
4
11
0
Order By: Relevance
“…Inorganic N and S deposition can enrich stemflow as well (Butler and Likens, 1995). Opportunities likely exist for stemflow signals to inform us regarding canopy water balances (isotopically: Allen et al, 2017;Pinos et al, 2022), the trapping and recycling of particulate aerosols (through its abiotic and biotic particulate matter content: Ponette-González, 2021), and the balance of canopy soils, where present (also through its particulate matter content).…”
Section: Signals From Biogeochemical Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Inorganic N and S deposition can enrich stemflow as well (Butler and Likens, 1995). Opportunities likely exist for stemflow signals to inform us regarding canopy water balances (isotopically: Allen et al, 2017;Pinos et al, 2022), the trapping and recycling of particulate aerosols (through its abiotic and biotic particulate matter content: Ponette-González, 2021), and the balance of canopy soils, where present (also through its particulate matter content).…”
Section: Signals From Biogeochemical Processesmentioning
confidence: 99%
“…Thus, stemflow (and throughfall) isotopic signals may aid in improving our understanding of the mechanisms driving evaporation and routing of precipitation in canopies. For example, recent results from within-storm monitoring of stemflow isotopic signals suggest that, since stemflow has longer residence times within the canopy than throughfall, it may yield strong inferences into the role of evaporation in fractionation (Pinos et al, 2022).…”
Section: Signals From Biogeochemical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…While throughfall amounts are well correlated to canopy structure, the isotopic composition of throughfall is not (Hsueh et al, 2016); thus, other, temporally varying controls are more important. Previous studies found that the isotopic offset between precipitation, throughfall and stemflow varies between seasons (Pinos et al, 2022) and also varies with rainfall characteristics, such as rainfall amount (Allen et al, 2015), duration (Liu et al, 2008), intensity (Dewalle & Swistock, 1994), and drop size (Pinos et al, 2020). While throughfall offsets have been widely reported, stemflow offsets have been less investigated (Allen et al, 2020;Pinos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the isotopic offset between precipitation, throughfall and stemflow varies between seasons (Pinos et al, 2022) and also varies with rainfall characteristics, such as rainfall amount (Allen et al, 2015), duration (Liu et al, 2008), intensity (Dewalle & Swistock, 1994), and drop size (Pinos et al, 2020). While throughfall offsets have been widely reported, stemflow offsets have been less investigated (Allen et al, 2020;Pinos et al, 2022). This is most likely due to the fact that stemflow typically occurs in small volumes (<2% of total incoming precipitation); nevertheless it can still contribute water and nutrients to the subsurface around tree stems (Carlyle-Moses & Gash, 2011;Snelgrove et al, 2020).…”
Section: Introductionmentioning
confidence: 99%